Architecture in the Islamic Vision - Wazeri, Yehia Hassan (Journal of Islamic Architecture, 2020)
The Qurâ€™an contains about eighteen verses that refer to the architecture of the earth. Nearly two hundred elements (terminologies) of architecture and town planning have been mentioned in the Quran. This paper aims to present examples from the Quran to shed light on the Islamic vision of architecture and art. It uses content analysis method to achieve the objective of the research. The analysis is done by studying and discussing verses of the Holy Quran, which is related to architecture and urbanism. One of the most important results of this research is to give distinct architectural and urban examples, include the following: building materials, environmental architecture, houses of insects, visual illusions in architecture, and the centrality of Mecca to the world. All of them is explained in the Qurâ€™an verses, such as Al-Baqarah, An-Naml, An-Nahl, Al-Kahf, and Al-Fajr.Â